Microcontroller based buck PID - Siti Jamilah, Mahful (2008)
This thesis revises of power electronic conversion techniques for switch-mode power converters for buck topology. Since the DC/DC converters are often used to provide a DC regulated output voltage, it also can be used to provide voltage isolation as well as the required regulated output voltage. The future project or demand is looking towards alternative power sources all of which will need to be regulated in one form or another with highest efficiency, high availability and high reliability with the lowest cost, smallest size and weight. Therefore, the parameters required for implement this converter based on system design. In addition to do this, the closed loop feedback system using PID controller method will be implement to against the voltage drop or load change in the system. This project perform is only limited to design the closed-loop feedback system using proportional technique for buck converter. The controller will be implemented on a PIC microcontroller (PIC18F4550) and programmed through a computer using software of Microcode Studio. The programmed PIC184550 will be able to automatically control the duty cycle of the system in order to apply an appropriate duty cycle to the system. The benefit of this project is result to improvement in percent overshoot depend on the voltage change and maintain output voltage needed.